The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/aac.06349-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Intravenous Ceftolozane-Tazobactam in Healthy Adult Subjects following Single and Multiple Ascending Doses

Abstract: The pharmacokinetics and safety of ceftolozane, a novel cephalosporin, and tazobactam, a ␤-lactamase inhibitor, alone and in combination as a 2:1 ratio in single doses of up to 2,000 and 1,000 mg of ceftolozane and tazobactam, respectively, and multiple doses of up to 3,000 and 1,500 mg of ceftolozane and tazobactam, respectively, per day were evaluated in healthy adult subjects. In part 1, groups of six subjects each received single ascending doses of ceftolozane, tazobactam, and ceftolozane-tazobactam in a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
128
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 9 publications
12
128
1
1
Order By: Relevance
“…One possible reason might be that the doses used in our study were low enough not to show any; in the study by Bulik et al, the dosing regimens were adjusted by lowering the dose but giving doses more often to account for drug interactions. In humans, such a drug interaction is not observed (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason might be that the doses used in our study were low enough not to show any; in the study by Bulik et al, the dosing regimens were adjusted by lowering the dose but giving doses more often to account for drug interactions. In humans, such a drug interaction is not observed (9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is not clear whether pharmacokinetic interactions exist between cephalosporins and tazobactam. In one earlier, limited study, such a pharmacokinetic interaction was observed between these two compounds (8) in mice, although it was not observed in men (9). Thus, the primary objectives of this study were to evaluate the pharmacokinetic profiling of ceftolozane and tazobactam in the mouse plasma and ELF and to assess potential drug interactions using a neutropenic murine thigh or lung infection model.…”
mentioning
confidence: 99%
“…1 Overall, the terminal half-life is approximately 2.5 hours for ceftolozane and 1 hour for tazobactam. [2][3][4] The C max and AUC increased in proportion to dose, while the elimination half-life was independent of dose. 1,3 In patients with normal renal function, the pharmacokinetics of ceftolozane/tazobactam are linear across a large range of doses.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…[2][3][4] The C max and AUC increased in proportion to dose, while the elimination half-life was independent of dose. 1,3 In patients with normal renal function, the pharmacokinetics of ceftolozane/tazobactam are linear across a large range of doses. [2][3][4] Steady-state volume of distribution in healthy adults was 13.5 L for ceftolozane and 18.2 L for tazobactam.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation